Occurrence and Characteristics of Microplastics in Leachate at a Large Municipal Wastewater Treatment Plant - Ormaniec, Paulina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the widespread occurrence and the potential threat to the environment, plastic materials are currently a growing problem of environmental protection in the world. Plastics whit dimensions not exceeding 5 mm are called microplastics. One of the main sources of microplastics in the aquatic environment are municipal wastewater treatment plants.
Keywords: microplastics; wastewater treatment plant; leachate; mikroplastik; oczyszczalnia ścieków; odcieki